Microbiome and Microbial Pure Culture Study Reveal Commensal Microorganisms Alleviate Salmonella enterica Serovar Pullorum Infection in Chickens - Jianshen Zhu; Jinmei Ding; Kaixuan Yang; Hao Zhou; Wenhao Yang; Chao Qin; Liyuan Wang; Fuquan Xiao; Beibei Zhang; Qing Niu; Zhenxiang Zhou; Shengqing Yu; et al. (Microorganisms, 2024)
Pullorum disease, an intestinal disease in chickens caused by Salmonella enterica serovar pullorum (S. Pullorum), is a significant threat to the poultry industry and results in substantial economic losses. The bacteria’s transmission, both vertical and horizontal, makes it difficult to completely eliminate it. Control strategies for pullorum disease primarily involve stringent eradication programs that cull infected birds and employ antibiotics for treatment. However, eradication programs are costly, and antibiotic use is restricted. Therefore, developing alternative control strategies is essential. Increasingly, studies are focusing on modulating the gut microbiota to control intestinal diseases. Modulating the chicken gut microbiota may offer a novel strategy for preventing and controlling pullorum disease in poultry. However, the impact of S. Pullorum on the chicken gut microbiota has not been well established, prompting our exploration of the relationship between S. Pullorum and the chicken gut microbiota in this study. In this study, we initially analyzed the dynamic distribution of the gut microbiota in chickens infected with S. Pullorum. Alpha diversity analysis revealed a decrease in observed OTUs and the Shannon diversity index in the infected group, suggesting a reduction in the richness of the chicken gut microbiota due to S. Pullorum infection. Principal coordinate analysis (PCoA) showed distinct clusters between the gut microbiota of infected and uninfected groups, indicating S. Pullorum infection changed the chicken gut microbiota structure. Specifically, S. Pullorum infection enriched the relative abundance of the genera Escherichia-Shigella (65% in infected vs. 40.6% in uninfected groups) and Enterococcus (10.8% vs. 3.7%) while reducing the abundance of Lactobacillus (9.9% vs. 32%) in the chicken microbiota. Additionally, based on the observed changes in the chicken gut microbiota, we isolated microorganisms, including Bifidobacterium pseudolongum, Streptococcus equi and Lacticaseibacillus paracasei (L. paracasei), which were decreased by S. Pullorum infection. Notably, the L. paracasei Lp02 strain was found to effectively inhibit S. Pullorum proliferation in vitro and alleviate its infection in vivo. We found that S. Pullorum infection reduced the richness of the chicken gut microbiota and enriched the relative abundance of the genera Escherichia-Shigella and Enterococcus while decreasing the abundance of the anaerobic genus Lactobacillus. Furthermore, microbiota analysis enabled the isolation of several antimicrobial microorganisms from healthy chicken feces, with a L. paracasei strain notably inhibiting S. Pullorum proliferation in vitro and alleviating its infection in vivo. Overall, this research enhances our understanding of the interaction between gut microbiota and pathogen infection, as well as offers new perspectives and strategies for modulating the chicken gut microbiota to control pullorum disease.